Evolução das taxas de detecção de casos de hanseníase em menores de 15 anos no estado de Minas Gerais de 2001 a 2010 - Maria Aparecida Alves Ferreira (2012)
Introduction: Leprosy is a chronic infectious disease, consideredto be declining, although still prevalent in many parts of the world, including Brazil. Leprosy in children is a serious public health problem, as it points to infection in the community and the need to improve the efficacy of control programs. There is evidence that socio-economic factors influence the tendency of this secular disease. Objectives: to analyze the evolution of leprosy case detection rates in children under 15 in the state of Minas Gerais (MG) from 2001 to 2010; also,to investigate the influence of socio-economic characteristics of the municipalities in the occurrence of the disease. Methods: ecological study considering each municipality of the state as the unit of analysis. The outcome variable was the leprosy detection rate in children under 15 in each municipality. The explanatory variables were: Human Development Index (HDI), Gini index, gross domestic product (GDP) per capita, percentage of illiterate mothers or mother-in-laws 20 years of age or more, mean number of years of schooling of the heads of the households and child mortality rate. The detection rate was calculated annually and theme maps of the spatial distributionof the detection rates were produced for each year. The chi-square test for linear trend and the Zeros-inflated Poisson regression simple and multiple models were used for statistical analyses. Results: the leprosy case detection rates in children under 15 in Minas Gerais state showed a significant decline from 2004 on (p<0.001), although the detection coefficients remained in medium to high levels. This was also observed in the spatial distribution. In the simple Poisson model, the variables which showed association to the evolution of leprosy case detection in all studied years were: HDI, GDP per capita and mean years of schooling of the heads of the households with negative coefficients and percentage of illiterate mothers or mother-in-laws with a positive coefficient. Conclusions: the data showed a decline in leprosy case detectionin children under 15 in Minas Gerais state in the lastsix years studied. The evolution of the detection rates was influenced by socio-economic characteristics of the municipality population. The detection coefficientsremained in medium to high levels, reflecting early exposition, persistence of transmission in the community, and the need to re-evaluate the current control models.